Các nhân tố ảnh hưởng đến hành vi chơi game của học sinh tiểu học khi học trực tuyến - Nguyễn , Thị Hồng Chuyên; Trần , Ngọc Bích (Tạp chí Giáo dục, 2022)
Online learning is becoming increasingly popular in the 4th Industrial Revolution era. The Covid-19 pandemic has promoted online learning at all levels, from higher education to primary schools. Despite the many advantages of online learning, there exist certain limitations and challenges, one of which is making sure all students actively participate in online lessons. Video games and social media are distracting for kids when they study online in general, and elementary students in particular. It can be hard to keep track of whether your pupils are playing video games while they are supposed to be learning. The purpose of this study is to examine what factors encourage elementary school children to play video games while they are learning online. Exploratory Factor Analysis was used to analyze a sample of 430 parents in Vietnam with children in primary schools. Seven factors were found to influence students’ covert play during online primary school hours. A future research study will be recommended in order to develop effective strategies for monitoring online students based on the findings of this study.